Magnetoelectric interactions in bismuth sodium-potassium titanate-nickel cobalt ferrite lead-free composite ceramics - Camargo, Javier Eduardo (2020)
Bismuth sodium-potassium titanate (BNKT) and nickel-cobalt ferrite (NCF) ceramic composite materials (xBNKT-(100-x)NCF), with different ferrite proportions, were studied. Piezoelectric and ferrite powders were separately synthesized by the solid-state method. Structural analyses were carried out by X-ray diffraction and Raman spectra studies of the composites whereas microstructural studies were performed by Scanning Electron Microscopy and the element distribution was studied by Energy Dispersive X-Ray Spectroscopy. Dielectric permittivity and loss values were sensitive to temperature and composition variations. Magnetic and magnetoelectric properties of the xBNKT-(100-x)NCF composites have been investigated. Ions diffusion and chemical reaction between BNKT and ferrite phases cause microstructural and structural variations that are responsible for moving away from the saturation magnetization from those calculated. Moreover, microstructural evolution controls the magnetoelectric properties of these lead-free composites.